An updated review of worldwide levels of docosahexaenoic and arachidonic acid in human breast milk by region. Issue 15 (8th April 2016) - Fu, Yuanqing; Liu, Xin; Zhou, Bing; Jiang, Alice C; Chai, Lingying
Abstract: Objective: We aimed to evaluate the DHA and arachidonic acid (AA) levels in human breast milk worldwide by country, region and socio-economic status. Design: Descriptive review conducted on English publications reporting breast-milk DHA and AA levels. Setting: We systematically searched and identified eligible literature in PubMed from January 1980 to July 2015. Data on breast-milk DHA and AA levels from women who had given birth to term infants were included. Subjects: Seventy-eight studies from forty-one countries were included with 4163 breast-milk samples of 3746 individuals. Results: Worldwide mean levels of DHA and AA in breast milk were 0·37 (sd 0·11) % and 0·55 (sd 0·14) % of total fatty acids, respectively. The breast-milk DHA levels from women with accessibility to marine foods were significantly higher than those from women without accessibility (0·35 (sd 0·20) % v . 0·25 (sd 0·14) %, P <0·05). Data from the Asian region showed the highest DHA concentration but much lower AA concentration in breast milk compared with all other regions, independent of accessibility to marine foods. Comparison was made among Canada, Poland and Japan – three typical countries (each with sample size of more than 100 women) from different regions but all with high income and similar accessibility to fish/marine foods. Conclusions: The current review provides an update on worldwide variation in breast-milk DHA and AA levels and underlines the need for future population- or region-specific investigations.